Learning to create eBooks - Anderson, Andy (InfiniteSkills, 2013)
"In this ePub training course, Andy Anderson will teach you how to create and publish eBooks using Adobe InDesign. eBooks are a powerful way to publish your document, be it a book, instruction manual or just a personal journal for your own personal perusal. You can distribute it using a number of different methods which Andy covers in this course. You will start by setting up an InDesign template for your ePub. You will import the text and work with character and paragraph styles for your publication. You will learn how to do basic formatting, add page breaks and a table of contents. Andy shows you how to add and optimize images in your eBook, and how to export and proof your ePub. This video tutorial covers methods of publishing your eBook to Kindle, iTunes, working with alternate ePub formats, generating externals links, and much much more. Once you have completed this computer based training course, you will understand the tools and techniques that you need in order to start publishing your own eBooks. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page